Influence of Electromagnetic Waves with Extremely High Frequencies on Some Criteria of Blood Plasma - Nerkararyan, A. V.; P. O. Vardevanyan; A. P. Antonyan; M. A. Parsadanyan; M. A. Shahinyan; M. R. Darbinyan; M. S. Mikaelyan
The effect of electromagnetic waves of extremely high frequencies (EMW EHF) on the blood plasma surface tension coefficient and the albumin denaturation parameters was studied. It was shown that blood plasma irradiation, taken from rats, results in significant increasing of its surface tension coefficient value compared to that of nonirradiated samples. It was also shown that a reliable difference between irradiated samples by 41.8 GHz and 51.8 GHz frequencies was not noticed. Albumin solution denaturation parameters under to irradiation were studied. It was shown that protein denaturation curve shifting to high temperature region occurs which means that stabilization of protein structure takes place. It was shown that protein denaturation curve shifts to high temperature region, which means that stabilization of protein structure, takes place.
Keywords: Physics; Cross-Disciplinary